2010
DOI: 10.1002/jbm.a.32718
|View full text |Cite
|
Sign up to set email alerts
|

In vivo wound healing and antibacterial performances of electrospun nanofibre membranes

Abstract: In this work, nanofibre membranes have been produced from polyvinyl alcohol (PVA), polycaprolactone (PCL), polyacrylonitrile (PAN), poly (vinylidene fluoride-co-hexafluoropropene) (PVdF-HFP), and polymer blend of PAN and polyurethane (PEU) using an electrospinning technique, and wound healing performance of the as-spun nanofibre membranes was examined in vivo using female Sprague-Dawley rats. To understand the nutrition effect, a wool protein was coated on PVA and PCL nanofibres and incorporated into PVA nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 27 publications
(59 reference statements)
2
141
0
Order By: Relevance
“…The current aim is to develop systems that not only target various components of the wound healing process (i.e., anti-inamma-tory and antibacterial activity) but also provide an adjustable and controlled release of multiple drugs. 119 The amount and progression (be that simultaneous or a stepwise release) of drugs will be determined by the stage of the healing wound.…”
Section: Emerging Nanober Mats That Strategically Target Multiple Famentioning
confidence: 99%
“…The current aim is to develop systems that not only target various components of the wound healing process (i.e., anti-inamma-tory and antibacterial activity) but also provide an adjustable and controlled release of multiple drugs. 119 The amount and progression (be that simultaneous or a stepwise release) of drugs will be determined by the stage of the healing wound.…”
Section: Emerging Nanober Mats That Strategically Target Multiple Famentioning
confidence: 99%
“…40,41 It is also possible to use functionalized solvents to carry charge. 42 All of these routes allow the formation of perfluorinated fibers on one step, although any other fibers can be treated in a second step coating a finished mat.…”
Section: Electrospinningmentioning
confidence: 99%
“…The air permeability is one of the important parameters of wound dressings, which prevents maceration and (2) gives a better comfort to the patients. In a recent in vivo study on wound healing and antibacterial performance of electrospun nano fibre membranes, the authors concluded that the porosity and air permeability characteristics have a strong influence on facilitating the wound healing, especially at the early healing stages (3). It can also be noticed from the data in Table 1 that the air-permeability values of the fabrics increased when the fabrics' area densities decreased.…”
Section: Flexural Rigidity and Air Permeabilitymentioning
confidence: 96%